2022
DOI: 10.1136/tobaccocontrol-2021-056575
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation: health system challenges and opportunities

Abstract: The systematic integration of evidence-based tobacco treatment has yet to be broadly viewed as a standard-of-care. The Framework Convention on Tobacco Control recommends the provision of support for tobacco cessation. We argue that the provision of smoking cessation services in clinical settings is a fundamental clinical responsibility and permits the opportunity to more effectively assist with cessation. The role of clinicians in prioritising smoking cessation is essential in all settings. Clinical benefits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 97 publications
(149 reference statements)
1
46
0
Order By: Relevance
“…Smoking cessation is the most powerful and cost-effective intervention, which improves the overall health and quality of life among smokers, especially those with NCD 34 . In this study, less than half of current smokers had intention to quit in a year, which was lower than the findings in previous studies 15 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation is the most powerful and cost-effective intervention, which improves the overall health and quality of life among smokers, especially those with NCD 34 . In this study, less than half of current smokers had intention to quit in a year, which was lower than the findings in previous studies 15 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that smokers with NCD were more sensitive to the assumed smoking cessation advice from physicians, these findings are consistent in the subgroup analysis (both in male and female smokers, and in smokers of all ages), this might be due to the fact that smokers with NDC were worried about their disease progression. A previous study showed that illness can be a powerful motivation to quit among smokers 9 . So, in order to curb the high smoking prevalence and promote smoking cessation, it is crucial to pay special attention to smokers with NCD, provide professional smoking cessation counselling, psychological support and individualized treatment based in the clinical setting, which can effectively improve the success of smoking cessation among current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The finding in this study was in line with previous studies 5,22 . A robust body of literature has demonstrated that brief smoking cessation advice from a healthcare provider during usual medical consultation could encourage smoking cessation 9,20,21,39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations